1981
DOI: 10.1111/j.1095-8312.1981.tb00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive success and risk of predation in normal and melanistic colour morphs of the adder, Vipera berus

Abstract: I n a population of adders (Vipers b e w ) in Southwest Sweden, melanistic males were heavier than normal coloured males of the same length. Victory in male-male sexual combats was positively related to size. Higher risk ofpredation in the black morph was inferred from experiments showinga high predator attack rate on models of the black morph. Even the bright colour in newly moulted basking males of the normal morph gives cryptic protection. In females, melanism probably also attects body size and risk of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
123
7
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 17 publications
1
123
7
1
Order By: Relevance
“…Andrén & Nilson 1981;Luiselli 1992;Shine & Madsen 1994). However, in our study, the avoidance of 'adder' models was in fact more pronounced on a plain card background than on a natural background.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Andrén & Nilson 1981;Luiselli 1992;Shine & Madsen 1994). However, in our study, the avoidance of 'adder' models was in fact more pronounced on a plain card background than on a natural background.…”
Section: Discussioncontrasting
confidence: 64%
“…Our results also call for a re-evaluation of hypotheses on the causation of pattern polymorphism, and especially melanism, in V. berus. Andrén & Nilson (1981) sought to explain different predation rates between models of patterned and melanistic adders in the context of a tradeoff between the benefits of crypsis in zigzag patterned adders and the thermoregulatory benefits of melanism, resulting in faster growth but higher mortality in melanistic adders. However, their models were all positioned on a natural background, confounding the effects of crypsis (model not seen) and aposematism (model seen but avoided).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed in molluscs (Jones et al 1977;Goodhart 1987), reptiles (Andre´n and Nilson 1981), anurans (Hoffman and Blouin 2000), insects (Wilson et al 2001), birds (Roulin 2004) and plants (Armbruster 2002) showed that many genetic colour polymorphisms are not selectively neutral with respect to life history components, since alternative morphs are frequently observed to achieve a different reproductive success. This can often be explained by non-random habitat distribution of individuals with respect to colour morphs (Roulin 2004), suggesting that morphs are under disruptive selection by being adapted to alternative ecological niches.…”
Section: Introductionmentioning
confidence: 99%
“…Insets show a typically colored snake (lower left, photo by E Mizsei) and a black-colored individual (top right, photo by D Jablonski), both photographed in Albania. solar radiation, or higher reproductive success, but it also brings some disadvantages such as high predation risk, or is even nonadaptive (Andrén and Nilson, 1981;Capula and Luiselli, 1994;Rosenblum, 2005;Millien et al, 2006;Lorioux et al, 2008). Luiselli (1995) discussed melanistic individuals of Hierophis viridiflavus/carbonarius especially regarding advantages for reproduction.…”
mentioning
confidence: 99%